Elbow Dysplasia in German Shepherd in Turkey - Durmus, Ali Said; Han, Mehmet Cengiz (Medwell Online, 2010)
Clinical and radiographic diagnostic methods and incidence of elbow dysplasia in German shepherds has been discussed in this study. About 284 elbow joints of 142 German shepherd dogs (different age and sex) consisted the material of the study. After radiological examinations types and the degrees of the dysplasia were identified. Out of 142 dogs, 29 dogs (20.42%) were found to be dysplasied. The results of the present study show that elbow dysplasia is a significant problem in German shepherd dogs in Turkey.
Keywords: Elbow dysplasia; radiographic diagnosis; German shepered dogs; UAP; OCD; Turkey